Epidemiology and Natural History of Childhood-Acquired Chronic Hepatitis C: A Single-Center Long-Term Prospective Study. Issue 2 (1st June 2022) - Stinco, Mariangela; Bartolini, Elisa; Veronese, Piero; Rubino, Chiara; Moriondo, Maria; Ricci, Silvia; Trapani, Sandra; Azzari, Chiara; Resti, Massimo; Indolfi, Giuseppe
Abstract : Objectives: To prospectively describe the epidemiology and long-term outcome of childhood-acquired hepatitis C virus (HCV) infection in a large cohort of children followed at a single center. Methods: All children with chronic HCV infection followed at the Liver Unit of our tertiary Hospital in Florence (Italy) from January 1, 1988, to September 30, 2021, were included in the analysis. Results: The final sample consisted of 163 children (median age at enrollment 4 years, interquartile range (IQR): 10; median age at last follow-up 14 years, IQR: 7). The median duration of follow-up was 86 months (IQR: 112). One hundred twenty-five children were vertically infected and 26 acquired the infection horizontally. Twenty-six of the 125 children who were vertically infected (20.8%) underwent spontaneous clearance of HCV RNA at a median age of 4 years (IQR: 2), whereas all the others remained persistently viremic. One patient was diagnosed with cirrhosis; 2 presented clinically detectable extrahepatic manifestations (chronic urticaria). Thirty-two children (19.6%) received antiviral therapy: 8 out of 32 (25%) were treated with pegylated-interferon alfa-2b [sustained virological response (SVR) 24 weeks after the end of treatment in 7/8]; 24 out of 32 (75%) were treated with direct-acting antivirals (SVR 12 weeks after the end of treatment in 23/24). Conclusions: The present study describes the largest cohort of children with chronic HCV infection prospectively evaluated with a long follow-up at a single center. HCV infection in children is often a chronic infection that can be cured with modern antiviral therapy. Early treatment could prevent the development of advanced liver disease.